Enhancing EFL Academic Writing Through Video-Based Summarization Tasks: Evidence From Non-English Major Undergraduates - Syaadiah Arifin; Risna Saswati (PROJECT (Professional Journal of English Education), 2026)
Academic summary writing remains a demanding skill for many non-English-major students because it requires learners to understand source content, identify main ideas, organize information, and reformulate meaning in a coherent written form. This study investigated the use of video-based summarization tasks to enhance academic summary writing among Indonesian EFL undergraduates from non-English departments. Employing a quasi-experimental mixed-methods design, the study involved 50 second-semester students from the Faculty of Social and Political Sciences at an Indonesian university. The students were divided into an experimental group, which completed video-based summarization tasks, and a control group, which completed text-based summarization tasks. Students’ summaries were assessed using an analytic rubric covering coherence, paragraph organization, lexical resource, grammatical accuracy, and task fulfilment. The findings showed that the experimental group achieved greater improvement than the control group in coherence, paragraph organization, lexical resource, and task fulfilment, while grammatical accuracy did not improve significantly. Questionnaire and interview data further indicated that video-based tasks increased students’ motivation, vocabulary development, structural awareness, and writing confidence. These findings suggest that story-based video materials can provide useful contextual and emotional support for EFL learners in academic summary writing.